Respostas
Resposta:
Explicação passo-a-passo:
1) a) [ m 7] = [ 8 7 ]
[ n -1] [ 9 -1 ]
m = 8
n = 9
b) [ m 2n ] = [ 4 -n 2 ]
[ 9 -1 ] [ 9 -1 ]
2n = 2
n = 2
2
n = 1
m = 4 - n
m = 4 - 1
m = 3
______________________________________________________
2)
a) (2) + (1 ) = ( 3 )
(8) (2 ) ( 10 )
b) (10 5 ) + ( 2 -6 ) = ( 12 - 1 )
(- 1 0 ) (-3 7 ) (-4 7 )
c) ( 7 0 ) + ( 1 3) = ( 8 3 )
______________________________________________________
3) ( a b ) + ( 2 - 1 ) = ( 5 8 ) + ( 1 0 ) + ( -1 -6 )
( 6 c ) ( 3 4 ) ( 4 0 ) ( 3 2 ) ( 2 5 )
a + 2 = 5 + 1 - 1
a = 5 + 1 - 1 - 2
a = 3
b - 1 = 8 + 0 - 6
b = 8 + 0 - 6 +1
b = 3
c + 4 = 0 + 2 + 5
c = 0 + 2 + 5 - 4
c = 3
Resposta:
Ver abaixo
Explicação passo-a-passo:
1a) m = 8 e n = 9
1b) 2n = 2 --> n = 2/2 --> n = 1
m = 4 - n --> m = 4 - 1 --> m = 3
2a)
2b)
2c)
3)
Logo, a = b = c = 3
*** Quando a opção estiver disponível, não se esqueça de escolher uma das respostas como a melhor ***